1984
DOI: 10.1111/j.1445-5994.1984.tb03778.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Oral Treatment of Severe Paget's Disease of Bone With Apd (3‐amino‐i‐hydroxypropylidene‐1,1‐bisphosphonate); A Comparison With Combined Calcitonin + Ehdp (1 ‐hydroxyethylidene‐1,1 ‐bisphosphonate)

Abstract: Ten patients with severe Paget's disease of bone and serum alkaline phosphatase (sAP) greater than 900 IU/l were treated for six months with the oral diphosphonate APD, (3-amino-1-hydroxypropylidene-1, 1-bisphosphonate). By the end of the treatment period there was a reduction in the log mean urine hydroxyproline (uHP) and the log mean sAP of 92% and 87% respectively. In four patients both sAP and uHP fell to within the normal range and remained normal for at least six months after therapy was stopped. Bone sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…It is noteworthy that, while all our patients responded biochemically and all those with radiographic lytic bone lesions demonstrated a positive response, few of the patients for whom biopsy information was available achieved normal-ization of histomorphometric indices (Fig. 3), despite some improvement in all indices in both the mild-moderate and severe groups . Fraser et al (1984) also found a lack of significant histomorphometric changes in six patients after APD therapy.…”
Section: Dlscusslonmentioning
confidence: 71%
See 1 more Smart Citation
“…It is noteworthy that, while all our patients responded biochemically and all those with radiographic lytic bone lesions demonstrated a positive response, few of the patients for whom biopsy information was available achieved normal-ization of histomorphometric indices (Fig. 3), despite some improvement in all indices in both the mild-moderate and severe groups . Fraser et al (1984) also found a lack of significant histomorphometric changes in six patients after APD therapy.…”
Section: Dlscusslonmentioning
confidence: 71%
“…One of the newer bisphosphonates, 3-amino-1-hydroxypropylidene-I , I-bisphosphonic acid (APD) attaches to bone matrix and inhibits osteoclast activity both directly and by preventing recruitment and differentiation of precursor mononuclear cells (Boonekamp et al, 1986;Lowik et al, 1988). The use of APD in the treatment of Paget's disease permits bone turnover to be reduced to an average of 30% of pretreatment levels (Fraser et al, 1984;Adami et al, 1986;Harinck et al, 1987a. b).…”
mentioning
confidence: 99%
“…Indeed, etidronate has been shown to increase the fracture risks in these patients [19]. However, the newer generation of bisphosphonates such as pamidronate (clodronate and residronate), has been reported to improve healing of osteolytic lesions [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates have been used successfully for the treatment of HM over the past few years (Fleisch, 1982;Fraser et al, 1984;Wimalawansa, 1993Wimalawansa, , 1994. In most countries, calcitonin and at least one of the parenterally administered bisphosphonates are now approved for the treatment of HM (Wimalawansa, 1989;1993).…”
Section: Present Affiliation and Address For Correspondence: Dr Sunilmentioning
confidence: 99%
“…In patients with severe hypercalcaemia in whom the plasma calcium level needs to be reduced rapidly, combined treatment with calcitonin and bisphosphonate is safe and highly effective (Fraser et al, 1984;Ralston et al. 1986;Wimalawansa, 1993).…”
Section: Dlscuerionmentioning
confidence: 99%